Analisis Jumlah Kendaraan Bermotor Dari Kegiatan Transportasi Di Kota Pasir Pengaraian - Muhammad Taslim; Aryo Sasmita; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
One of the decreases in environmental quality is caused by pollution of carbon dioxide (CO2) from transportation activities. Pasir Pengaraian City is one of the cities that has potential as a producer of carbon dioxide (CO2) emissions from transportation activities in Riau Province. One effort to reduce the concentration of CO2 in urban air is by applying the concept of green area or better known as green open space (GOS). This study aims to determine the number of motorized vehicles from transportation activities in the city of Pasir Pengaraian. The method used, which is recording traffic activities to calculate the amount of CO2 emissions. the results showed that the number of densest vehicles for arterial and collector roads occurred on Sunday with a total of 16,886 vehicles / day for arterial roads and 10,883 vehicles / day for collector roads, whereas for local roads, the number of densest vehicles occurred on Monday, with the number of vehicles is 3,392 vehicles / day.Keywords: Motorized Vehicles, Carbon Dioxide (CO2), Pasir Pengaraian City